2020
DOI: 10.1093/jtm/taaa153
|View full text |Cite
|
Sign up to set email alerts
|

Call to avert acceleration of COVID-19 from India’s Sabarimala pilgrimage of 25 million devotees

Abstract: Highlights India has the third-highest COVID-19 burden. Hosting the Sabarimala pilgrimage of an estimated 25 million can compromise the near-mitigated but fragile COVID-19 status of the host State of Kerala, accelerate the ongoing outbreaks in other states of India, and potentially in multiple countries with emigrants from Kerala.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“… 68 There was also a call to act to mitigate potentially serious consequences of the Hindu pilgrimage in India. 69 …”
Section: Public Health Emergency Of International Concern (Pheic)mentioning
confidence: 99%
“… 68 There was also a call to act to mitigate potentially serious consequences of the Hindu pilgrimage in India. 69 …”
Section: Public Health Emergency Of International Concern (Pheic)mentioning
confidence: 99%
“…The state of Kerala (population 34 million) was the first to report the Corona Virus Disease 2019 (COVID-19) case in India on January 30, 2020 in three medical students who returned from Wuhan, China [1]. Prompt quarantine measures effectively stopped transmission from these cases.…”
Section: Introductionmentioning
confidence: 99%
“…Kerala was the first state to report COVID-19 in India on 30 January 2020 that prompted the state to be a trailblazer in pandemic mitigation in India and the State achieved successful pandemic mitigation (zero cases reported on 3 May 2020), hailed as a model for India. 3 However, Kerala’s COVID-19 cases exponentially increased in later months (10 000 cases/day on 7 October 2020, 8402 cases per million). Phylogenetic studies revealed that Kerala’s resurgence of cases may have originated from internal transmission within India than from returning international emigrants.…”
mentioning
confidence: 99%